Older adults show higher increases in lower-limb muscle activity during whole-body vibration exercise. (8th February 2017) - Lienhard, Karin; Vienneau, Jordyn; Nigg, Sandro; Friesenbichler, Bernd; Nigg, Benno M.
Abstract: The purpose of this study was to compare lower limb muscle activity during whole-body vibration (WBV) exercise between a young and an older study population. Thirty young (25.9±4.3 yrs) and thirty older (64.2±5.3 yrs) individuals stood on a side-alternating WBV platform while surface electromyography (sEMG) was measured for the tibialis anterior (TA), gastrocnemius medialis (GM), soleus (SOL), vastus lateralis (VL), vastus medialis (VM), and biceps femoris (BF). The WBV protocol included nine vibration settings consisting of three frequencies (6, 11, 16 Hz) x three amplitudes (0.9, 2.5, 4.0 mm), and three control trials without vibration (narrow, medium, wide stance). The vertical platform acceleration (peak values of maximal displacement from equilibrium) was quantified during each vibration exercise using an accelerometer. The outcomes of this study showed that WBV significantly increased muscle activity in both groups for most vibration conditions in the TA (averaged absolute increase: young: +3.9%, older: +18.4%), GM (young: +4.1%, older: +9.5%), VL (young: +6.3%, older: +12.6%) and VM (young: +5.4%, older: +8.0%), and for the high frequency-amplitude combinations in the SOL (young: +7.5%, older: +12.6%) and BF (young: +1.9%, older: +7.5%). The increases in sEMG activity were significantly higher in the older than the young adults for all muscles, i.e., TA (absolute difference: 13.8%, P <0.001), GM (4.6%, P =0.034), VL (7.6%, P =0.001), VM (6.7%, P =0.042), BF (6.4%, P <0.001), except for the SOL (0.3%, P =0.248). Finally, the vertical platform acceleration was a significant predictor of the averaged lower limb muscle activity in the young ( r =0.917, P <0.001) and older adults ( r =0.931, P <0.001). In conclusion, the older population showed greater increases in lower limb muscle activity during WBV exercise than their young counterparts, meaning that they might benefit more from WBV exercises. Additionally, training intensity can be increased by increasing the vertical acceleration load.